Patrons and viewers in late antiquity - Birk, Stine; Poulsen, Birte (Aarhus University Press, 2012)
"This book contains a collection of papers that focuses on the way patrons, pagan as well as Christian, conveyed messages through material and visual culture and on the reception by the viewers. The contributions investigate how patrons of luxurious buildings, elaborate grave monuments, and churches used architecture, images, and inscriptions to demonstrate political, social, and religious power. The visual arts were a strong factor in communicating identity and attitudes both in the public and private spheres also in Late Antiquity"--Page 4 of cover.
"This volume presents the proceedings of a conference on Patrons and viewers in Late Antiquity held at Aarhus University in October 2008"--Page 7.
Keywords: Art, Ancient -- Congresses.; Art patronage -- Congresses.; Art, Greek -- Themes, motives -- Congresses.; Art, Roman -- Themes, motives -- Congresses.; Art, Early Christian -- Themes, motives -- Congresses.; Art antique -- Congrès.; Mécénat -- Congrès.; Art romain -- Thèmes, motifs -- Congrès.; Art paléochrétien -- Thèmes, motifs -- Congrès.; HISTORY / Ancient / General; Art, Ancient; Art, Early Christian -- Themes, motives; Art, Greek -- Themes, motives; Art patronage; Art, Roman -- Themes, motives; Macht; Patronage; Architektur; Ausstattung; Darstellung; Spätantike; Römisches Reich; Conference papers and proceedings